p53 and mdm2 in mantle cell lymphoma in leukemic phase - M Solenthaler; E Matutes; V Brito-Babapulle; R Morilla; D Catovsky (Haematologica, 2002)
BACKGROUND AND OBJECTIVES: In mantle cell lymphoma (MCL), abnormalities additional to t(11;14) including those affecting genes involved in the p53 pathway, are important for disease development and progression. This study aimed to assess the frequency, relationship and impact of p53 abnormalities and those of its inhibitor mdm2 in blastoid and non-blastoid MCL in leukemic phase. DESIGN AND METHODS: Isolated blood lymphocytes from 21 patients with MCL in leukemic phase, characterized by the presence of t(11;14), were analyzed by flow cytometry and by fluorescent in situ hybridization in order to investigate whether there is a correlation between overexpression and deletion of p53, overexpression of mdm2 and gain of chromosome 12. Results were also correlated with morphologic subtypes, proliferative activity assessed by expression of Ki67 and clinical outcome. RESULTS: Cells from 2/21 (10%) and 7/21 (33%) patients overexpressed p53 and mdm2, respectively. No single case expressed both proteins. Ten out of 19 (53%) patients had a hemizygous loss of 17p (p53) including the 2 patients (11%) overexpressing p53. Gains of chromosome 12 (mdm2) were found in only 2 cases with expression of mdm2 in one of them. Overall, p53 deletion and/or overexpression of mdm2 was found in 71% of cases. Ten of 19 patients had a blastoid MCL, including all 5 patients who were Ki67 positive, 6 of the 7 patients expressing mdm2 and one of the 2 patients expressing p53. There was no correlation between p53 deletion and morphologic subtypes. All patients with blastoid MCL have died after a median time of 25 months. INTERPRETATION AND CONCLUSIONS: In MCL in leukemic phase there is a high frequency of p53 deletion and/or overexpression of mdm2. In contrast, over expression of p53 is relatively rare. Overexpression of mdm2 is seen predominantly in blastoid MCL, the latter being characterized by a short median survival, and seems unrelated to a numerical gain of chromosome 12. It does not reflect a high proliferative rate but might indicate an alternative mechanism of inactivating p53 in prognostically adverse types of MCL.